2022
DOI: 10.1097/mao.0000000000003780
|View full text |Cite
|
Sign up to set email alerts
|

The Demographics of Menière's Disease: Selection Bias or Differential Susceptibility?

Abstract: ObjectiveTo clarify whether the reported lack of racial and ethnic diversity among Menière's disease (MD) patients is representative of selection bias or disease susceptibility.Study DesignRetrospective medical record review and population-level analyses.SettingTertiary referral center.PatientsCohort of 1091 patients diagnosed with MD by the tertiary otology service.Main Outcome MeasureDemographic and population-level characteristics (age, sex, race, insurance status, ZIP code, median income, education level) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Although 806 patients were identified by ICD‐10 codes, we found that only ~60% of those patients had MD according to the current AAO‐HNS guidelines, with only ~20% meeting diagnostic criteria for definite MD. This further justifies and provides the impetus for this study, given that many prior epidemiologic studies of MD rely purely upon diagnostic codes within clinical records or national records systems, and few have applied strict MD diagnostic criteria 2,10–18 . The construct validity of such studies must thus be called into question due to their inclusion of conditions with overlapping symptomatology—such as vestibular migraine—among cohorts of “MD” 6–9 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Although 806 patients were identified by ICD‐10 codes, we found that only ~60% of those patients had MD according to the current AAO‐HNS guidelines, with only ~20% meeting diagnostic criteria for definite MD. This further justifies and provides the impetus for this study, given that many prior epidemiologic studies of MD rely purely upon diagnostic codes within clinical records or national records systems, and few have applied strict MD diagnostic criteria 2,10–18 . The construct validity of such studies must thus be called into question due to their inclusion of conditions with overlapping symptomatology—such as vestibular migraine—among cohorts of “MD” 6–9 .…”
Section: Discussionmentioning
confidence: 96%
“…This further justifies and provides the impetus for this study, given that many prior epidemiologic studies of MD rely purely upon diagnostic codes within clinical records or national records systems, and few have applied strict MD diagnostic criteria. 2,[10][11][12][13][14][15][16][17][18] The construct validity of such studies must thus be called into question due to their inclusion of conditions with overlapping symptomatology-such as vestibular migraine-among cohorts of "MD". [6][7][8][9] As an illustrative example, in the highly cited 1984 study by Wladislavosky-Waserman et al from the Mayo Clinic, up to one-third of the included patients had recurrent vertigo without any cochlear symptoms, and thus would not meet current diagnostic criteria for MD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some more recent studies have noted similar frequencies among men and women. A study in United States suggests that Meniere's disease susceptibility is highest in older populations, white race, from higher income and rural areas, with a female to male ratio of only 1.25 [7]. The population-based study in Taiwan also showed higher prevalence in rural areas, with a female to male ratio of 1.84 [5].…”
Section: Epidemiologymentioning
confidence: 99%